Clarifying the concepts of system maturity, system readiness and capability readiness through case studies - Tetlay, Abideen; John, Philip (Published and used by CSER 2009 with permission, 2010)
This paper clarifies the key concepts of System Maturity, System Readiness and Capability Readiness and refines their definitions. The authors have achieved this by analysing three high-profile defence projects as case studies. The following military based systems were chosen: Chinook Helicopter; Apache Helicopter; and the Type 45 Anti-Air Warfare Destroyer.
Keywords: System Maturity; System Readiness; Operational Capability; Capability Readiness